From Bola‐Surfactant Templated Bimetal Phosphites to the Design of Crystalline Inorganic Mesoporous Frameworks. Issue 21 (13th March 2017) - Huang, Hui‐Lin; Huang, Wen‐Yen; Wang, Sue‐Lein
Abstract: Reproducing inorganic modules in situ for pore augmentation of pure inorganic frameworks is challenging but can be a key to rational synthesis. After the first success of using monoamines of varied lengths as a template in producing a set of building blocks that led to a series of growing channels up to a 72‐membered ring (72R), research continued into those building blocks to seek any new topologies from them. In this study, another type of template is reported that can control the same building blocks to repeatedly form in situ. By using long linear‐chain bola‐type surfactants, two new bimetal phosphites, a monoclinic phase exhibiting remarkable quasi‐channels of 1.15 nm and an orthorhombic phase with 28R channels of 1.06 nm have been created. By taking them as the first members, two series of novel topologies can be devised, each having a general formula to predict the size and channel wall compositions. Abstract : Super bola : The use of bola‐type surfactant has not only successfully reproduced inorganic building modules that were previously observed in the NTHU‐13 system, but also provided two additional modules, leading to two new designable series with channel sizes spanning the micro‐ and mesoporous regimes.